The Effect Of Superitem Models And Problem-Based Learning On Students' Reasoning And Problem - Putri, Rafika; Rahmaini; Hasibuan, Eka Khairani (Yana Research, 2023)
This study aims to determine students' mathematical reasoning and problem solving abilities using Superitem and Problem Based Learning models in the subject of Relations and Functions in class VIII SMP Negeri 5 Seruway. This research methodology uses quantitative research with the type of research experimental research. Data collection was carried out using techniques: essay tests, interviews and observations. The population in this study were all students of SMP Negeri 5 Seruway in the odd semester of the 2021/2022 academic year, a total of 235 students. The subjects in this study were students of class VIII-1 and VIII-3 of SMP Negeri 5 Seruway, each class consisting of 28 students. Hypothesis testing using Variance Analysis. The findings of this study are: 1) There is an influence on the reasoning abilities and mathematical problem solving abilities of students who are taught with the Superitem learning model on Relations and Functions Material for Class VIII SMPN 5 Seruway; 2) There is an influence on students' reasoning abilities and mathematical problem solving abilities taught using the Problem Based Learning model on Relations and Functions for Class VIII SMPN 5 Seruway; 3) There is an influence of the reasoning abilities and mathematical problem solving abilities of students who are taught with the Superitem and Problem Based Learning models on Relations and Functions Materials for Grade VIII SMPN 5 Seruway.